Downscaling global land-use/cover change scenarios for regional analysis of food, energy, and water subsystems - Yourek, Matt; Liu, Mingliang; Scarpare, Fabio V.; Rajagopalan, Kirti; Malek, Keyvan; Boll, Jan; Huang, Maoyi; Chen, Min; Adam, Jennifer C. (Frontiers in Environmental Science, 2023)
Integrated assessment models (IAMs) capture synergies between human development and natural ecosystems that have important implications for the food-energy-water (FEW) nexus. However, lack of fine-scale representation of water regulatory structure and differences in landscape characteristics in IAMs impede their application to FEW impact studies in water-limited basins. To address this limitation, we developed a framework for studying effects of global change on regional outcomes for food crops, bioenergy, hydropower, and instream flows. We applied the new methodology to the Columbia River Basin (CRB) as a case study. The framework uses the Demeter land-use and land-cover change (LULCC) downscaling tool, which we updated so that water rights are spatially integrated in the land allocation process. We downscaled two LULCC scenarios (SSP2-RCP 4.5 and SSP5-RCP 8.5) under three levels of irrigation expansion: no expansion (historical extent), moderate expansion (all land presently authorized by a water right is irrigated), and maximum expansion (new water rights are granted to cover all irrigable land). The downscaled scenarios were evaluated using a hydrology-cropping systems model and a reservoir model coupled in a linear fashion to quantify changes in food and bioenergy crop production, hydropower generation, and availability of instream flows for fish. The net changes in each sector were partitioned among climate, land use, and irrigation-expansion effects. We found that climate change alone resulted in approximately 50% greater production of switchgrass for bioenergy and 20% greater instream flow deficits. In the irrigation-expansion scenarios, the combination of climate change and greater irrigated extent increased switchgrass production by 76%-256% at the cost of 42%-165% greater instream flow deficits and 0%-8% less hydropower generation. Therefore, while irrigation expansion increased bioenergy crop productivity, it also exacerbated seasonal water shortages, especially for instream use. This work provides a general framework for linking benchmark scenarios of LULCC to outcomes for regional FEW subsystems.